Conceptual Design of an Internet of Things (IoT)-Based Automatic Plant Irrigation System Using ESP8266 NodeMCU and the Blynk Platform - Sri Lestari Sitohang; Saliana Br Selian; Chokes Lumbantoruan; Dicky Wahyudi (Pascal: Journal of Computer Science and Informatics, 2026)
The increasing demand for efficient plant maintenance has accelerated the adoption of Internet of Things (IoT) technologies in smart agriculture. This paper presents a conceptual design of an IoT-based automatic plant irrigation system utilizing the ESP8266 NodeMCU microcontroller and the Blynk platform for remote monitoring and control. The proposed system design includes the selection of hardware components, namely the YL-69 soil moisture sensor, a 5 V relay module, and a DC 5 V submersible water pump, as well as the development of software architecture incorporating automatic irrigation control logic and Blynk widget configuration. The proposed architecture adopts a three-layer IoT model consisting of the device layer, the Wi-Fi communication layer, and the application layer implemented through the Blynk platform. The designed system is intended to automatically activate the water pump when the measured soil moisture falls below a predefined threshold and deactivate it once sufficient soil moisture has been achieved. In addition, users can monitor soil moisture conditions in real time and manually operate the irrigation system through the Blynk mobile application. A comparative analysis of existing IoT-based irrigation studies indicates that the proposed conceptual framework provides a comprehensive integration of hardware architecture, communication mechanisms, software workflow, and user interface design. Furthermore, the selection of ESP8266 NodeMCU and the Blynk platform offers advantages in terms of ease of implementation, low deployment cost, scalability, and user-friendly operation. Although this study is limited to the conceptual design stage without prototype implementation or experimental validation, the proposed framework can serve as a practical reference for future development and implementation of IoT-based automatic irrigation systems.